ORGANIZING OF SANITARY-AND-QUARANTINE CONTROL IN PASSING POINT «BLAGOVESHSCENSK» - T. A. Stepykina; T. V. Bulatova (Acta Biomedica Scientifica, 2020)
Blagoveshchensk City has the border with PRC along the Amur River and has principal international contacts with this country, where epidemic situation for «atypical pneumonia» became complicated and threat of this infection delivery to the Amur region arose. All the year round transportations are held through the passing point «Blagoveshchensk» by water during navigation period and by iceroad in winter. Technological plans for passing people, loads and transport over the border are prepared taking into account this regime. Formed situation concerning SARS in SouthEastern Asia countries needed additional antiepidemic and preventive measures. The control after passengers was increased, medical examination was held with obligatory thermometry of all people from abroad. Individuals with fever were not admitted to pass the border, and Russian tourists were placed to insulator. The system of monitoring of RF citizen departure to central and southern China provinces is developed and introduced. The resources of individual protection were restocked, desinfection regime was brought in, medical insulator was managed. The cooperation of all control services was regulated. Rational principles of sanitaryandquarantine control organizing in the passing point allowed to prevent the delivery and spreading of SARS on the territory of RF.